Problems of Design and Construction of Buildings and Structures in Seismic Areas, on Weak Moistened Clay and Subsidence Loess Bases - Khakimov Gayrat Akramovich; Baymatov Shaxriddin Xushvaqtovich; Rakhimov Sherzod Abduvakhobjonovich; Tulyaganov Zafar Sunnatovich; Adilkhanova Zarofatkhan (Scientific Trends, 2024)
This article presents the features of the design and construction of buildings and structures on weak clay and subsident loess soils in seismic areas. A recommendation is given on vibration compaction of weak moistened clay and subsident loess soils of the foundations of buildings and structures, as well as bulk soils filled up around the foundation in seismically active areas.
Keywords: Weak clay soil, subsident loess soil, bulk soil, seismic areas, earthquakes, precipitation and subsidence, vibration method, seismic deformation, acceleration, strength characteristics of soils, foundations.